Peru : Monetary and Exchange Rate Policies, 1930-1980 - Pastor Campos, Gonzalo (IMF Working Papers; Working Paper, 2012)
This paper reviews monetary and exchange rate policies in Peru in 1930-80. The review covers major transformations to the world economy, including the post-1929 crash and WWII, and changing economic paradigms, such as the collapse of the gold standard and the rise and fall of the Bretton Woods system of fixed exchange rates. The analysis emphasizes the lasting partnership between Peruvian policymakers and the Bretton Woods institutions, while stressing the local authorities' ownership of final policy decisions. The review shows that, in general, during the fifty year period under analysis, the Peruvian authorities sought to deliver nominal exchange rate stability, even at the cost of introducing market distortions and/or incurring heavy losses in international reserves.